Effects of alpha lipoic acid as an antioxidant in preventing renal mitochondrial oxidative damage in diabetic rats - Noraihan binti Mat Harun (Kulliyyah of Medicine, International Islamic University Malaysia, 2012)
Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia due to inadequate secretion of insulin or insufficient action of the endogenous insulin. Oxidative stress has an important role in the pathogenesis of diabetic complications and mitochondria represent a major source of the reactive oxidants that lead to cellular oxidative damage. This study is design to observe the effect of alpha lipoic acid (ALA) as mitochondrial antioxidant in preventing renal mitochondrial oxidative damage in diabetic induced rats. In this study, the rats were divided into three groups. Normal Control (NC) group was served as a control; Diabetic Control (DC) group was induced for diabetes without given any supplementation, while Diabetic-Alpha Lipoic Acid (D-ALA) group was streptozotocin-induced diabetic rats, supplemented with ALA daily for six weeks. The ability of ALA in preventing renal mitochondrial oxidative damage was evaluated by comparing the renal function in terms of serum urea, serum creatinine and creatinine clearance in both supplemented and nonsupplemented rats, as well as mitochondrial H202 concentration and GSH/GSSG ratio as parameters for the oxidative stress. The results showed that ALA capable to ameliorate the defective antioxidant defense system leads to modulate the oxidative stress in terms of lower H202 concentration and higher GSH/GSSG ratio in D-ALA group compared with DC group. However the significant reduction of oxidative stress did not correlate well with the renal function parameters, in which only showed significant improvement of serum urea, but not serum creatinine or creatinine clearance. In conclusion, ALA treatment capable to ameliorate the defective antioxidant defense system and modulate the oxidative stress, but partially preventing the progression of renal dysfunction in diabetic rats.